The reality of applying entrepreneurial leadership in secondary schools in Jeddah from the teachers' point of view - Al-Salami, Abdulrahman Hamid (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the reality of applying entrepreneurial leadership in secondary schools in Jeddah from the teachers' point of view to achieve the objectives of the study, the descriptive analytical approach was employed. The questionnaire was used to collect data, and the results of the study revealed that the reality of appling of entrepreneurial leadership in secondary schools in Jeddah from the teachers’ point of view in the four dimensions of entrepreneurial leadership (entrepreneurial creativity, strategic vision, risk tolerance, and exploration of opportunities (initiative) was between high and meduim. There are no significant statistical significance differences between the average responses of the respondents about applying entrepreneurial leadership in the four dimensions of entrepreneurial leadership (entrepreneurial creativity, strategic vision, risk tolerance, and exploration of opportunities (initiative) among the principals of secondary education schools in Jeddah from the teachers’ point of view attributed to gender (male, female), and to the type of preparation (educational, non-educational). The study recommended the implementation of workshops and training courses for school leaders and leaders, and the development of indicators and criteria for pioneering leadership and effective leadership that believes in the importance of development, and is characterized by flexibility in thinking, risk tolerance, sensitivity to problems, and openness to new experiences.
Keywords: Entrepreneurial leadership; entrepreneurial creativity; strategic vision; risk taking; exploring opportunities